Measuring the non-linear effect of Chinese investment flows on the sustainable environment of BRI countries: Evidence from the lens of asymmetric approaches - Yufeng Chen; Zia Ur Rahman; Md Saiful Islam (Sustainable Futures)
Under the Belt and Road Initiative (BRI), implementing low-carbon economic cooperation is crucial to combating climate change and preserving sustainability worldwide. The paper checks the asymmetric (non-linear) effects of Chinese FDI flows on carbon dioxide (CO2) emissions to 24 selected nations from the Middle East, North Africa, and Asia regions. The study used the non-linear panel-ARDL and asymmetric causality methods to check the asymmetric relations. The result from the non-linear panel-ARDL method showed that positive (negative) shocks in Chinese FDI have positive effects on CO2 in the long run. The empirical outcomes estimated via the linear approach indicated that a rise in Chinese FDI would decrease CO2, thus supporting the pollution halo effect. Moreover, an increase (decrease) in economic growth significantly raises (decline) in CO2. From the Granger causality of Hatemi-J, a unidirectional causality is noted from the population (positive shock) and economic growth (positive shock) to CO2 (positive shock). The findings suggest that officials should entice FDI cautiously toward clean production and energy-saving industries and technology.